2012
DOI: 10.1080/19406940.2012.674962
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the community through sport club partnerships

Abstract: This article examines the nature of community sport connections evidenced by relationships between community sport clubs and various organizations in the community. This article uses a social capital perspective to highlight the potential of interorganizational relationships through sport as a mechanism for generating community connections and social cohesion. The findings of interviews with 20 club presidents illustrate how interorganizational relationships connect sport with the broader community as clubs re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 28 publications
1
45
0
1
Order By: Relevance
“…Trust, at one level, involves an appropriate degree of respect and courteousness between those committed to work together on a project (Barber et al 2011). Trust, cooperation and friendship, for example, are proposed as building blocks for collective action towards the promotion of a range of sport and non-sport-related outcomes in alliances between sport clubs and other community organisations (Misener and Doherty 2012) Yet trust in RPP partnerships also operates at an ethical level in terms of confidentiality, consent and discretion. The relationship between reciprocity and trust then should be thought of as going beyond the boundaries of politeness and into the maelstrom of honesty and integrity which are framed by an open approach to partnership working; one which reflects a moral code of carefulness, exactitude and veracity no matter how difficult decisions might become.…”
Section: Reciprocitymentioning
confidence: 99%
“…Trust, at one level, involves an appropriate degree of respect and courteousness between those committed to work together on a project (Barber et al 2011). Trust, cooperation and friendship, for example, are proposed as building blocks for collective action towards the promotion of a range of sport and non-sport-related outcomes in alliances between sport clubs and other community organisations (Misener and Doherty 2012) Yet trust in RPP partnerships also operates at an ethical level in terms of confidentiality, consent and discretion. The relationship between reciprocity and trust then should be thought of as going beyond the boundaries of politeness and into the maelstrom of honesty and integrity which are framed by an open approach to partnership working; one which reflects a moral code of carefulness, exactitude and veracity no matter how difficult decisions might become.…”
Section: Reciprocitymentioning
confidence: 99%
“…Prior literature on community sport clubs indicates infrastructure and process capacity to be a relatively small challenge among clubs (Wicker & Breuer, 2011). At the same time, those lacking access to sport facilities (i.e., limited infrastructure capacity) often form additional inter-organizational partnerships (Misener & Doherty, 2012;. The emergent findings in this study on the perceived importance of strengthening infrastructure and process capacity for increased organizational capacity does not appear in prior capacity literature.…”
Section: Discussionmentioning
confidence: 61%
“…In a more recent study of community sport clubs, Misener and Doherty (2012) found Canadian sport clubs were involved in an average of six external partnerships.…”
Section: Internal Systems and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations